2015
DOI: 10.4269/ajtmh.13-0617
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate and Mosquito Vector Abundance on Sylvatic Arbovirus Circulation Dynamics in Senegal

Abstract: Abstract. Sylvatic arboviruses have been isolated in Senegal over the last 50 years. The ecological drivers of the pattern and frequency of virus infection in these species are largely unknown. We used time series analysis and Bayesian hierarchical count modeling on a long-term arbovirus dataset to test associations between mosquito abundance, weather variables, and the frequency of isolation of dengue, yellow fever, chikungunya, and Zika viruses. We found little correlation between mosquito abundance and vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 36 publications
(46 reference statements)
2
81
0
1
Order By: Relevance
“…Phylogenetic analysis indicates that the virus has been introduced into West Africa at least twice in the twentieth century [48] and that West Africa contains ZIKV strains that are distinct from those elsewhere in Africa [49]. Analyses of mosquitoes collected annually over the last fifty years in Kedougou, Senegal demonstrated that ZIKV is amplified in mosquito collections at approximately four year intervals, that rainfall is a positive predictor of ZIKV isolations in mosquitoes, and that there was little positive or negative association between amplification of ZIKV and of three other Aedes -borne arboviruses that circulate in the region, YFV, DENV-2 and CHIKV [50]. Moreover our field studies in Kedougou during the 2011 ZIKV amplification showed that the virus was present in all major land cover classes in the region but was detected significantly more often in the forest than in other land cover types [51].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis indicates that the virus has been introduced into West Africa at least twice in the twentieth century [48] and that West Africa contains ZIKV strains that are distinct from those elsewhere in Africa [49]. Analyses of mosquitoes collected annually over the last fifty years in Kedougou, Senegal demonstrated that ZIKV is amplified in mosquito collections at approximately four year intervals, that rainfall is a positive predictor of ZIKV isolations in mosquitoes, and that there was little positive or negative association between amplification of ZIKV and of three other Aedes -borne arboviruses that circulate in the region, YFV, DENV-2 and CHIKV [50]. Moreover our field studies in Kedougou during the 2011 ZIKV amplification showed that the virus was present in all major land cover classes in the region but was detected significantly more often in the forest than in other land cover types [51].…”
Section: Introductionmentioning
confidence: 99%
“…First, while the main transmission pathway for ZIKV is through a mosquito vector [predominantly Aedes aegypti or Aedes albopictus (13,14)], a feature which has its own type of well-studied model and behavior (14)(15)(16), it can also spread through sexual contacts (17,18). Second, the probability of sexual transmission is highly asymmetric between males and females.…”
mentioning
confidence: 99%
“…The virus is explosive and unprecedented pace in the pandemic reemergence nature [27]. Therefore, knowing the associated driving factors is unquestionable.…”
Section: The Ecosystem and Other Factorsmentioning
confidence: 99%